PENGARUH PEMBERIAN SIMPLISIA JANTUNG PISANG KEPOK TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POST PARTUM DI PBM NURHAYATI DAN KLINIK PRATAMA NINING PELAWATI KEC. LUBUK PAKAM TAHUN 2020 - Fadilah Widyaningsih; Tri Marini SN (COLOSTRUM JURNAL KEBIDANAN, 2020)
Banana blossom is a food that has many benefits and is easily obtained by the community because it can be easily planted in the yard of the house. Banana blossom processing in the community can be done by boiling and steaming. Banana blossom also contains protein, minerals (especially phosphorus, calcium and iron) and a number of vitamins A, B1 and C. There are many reasons for mothers do not give exclusive breastfeeding to their babies. However, what is most often found is insufficient breast milk. There are several factors that influence milk production, one of which is the food factor. One of the efforts to increase breastmilk production that will be carried out is by giving Kepok Banana blossom Simplicia. This study aims to determine the effect of Kepok banana blossom simplicia on increasing breast milk production in postpartum mothers at Nurhayati and Nining Pelawati Midwifery Pratama Clinic, Lubuk Pakam sub district in 2019. This type of research was a Quasi Experiment with a Non Equivalent Control Group design and purposive sampling. Samples were normal postpartum mothers from day 7 to day 21 with parity of 1-2 and were willing to take part in the study through informed consent. Based on the results of the Wilcoxon Rank test and the Mann-Whitney test, it was obtained a p-value of 0.000 (? <0.05), which means that there was a significant effect on the simplicia of Kepok banana blossom on increasing milk production in postpartum mothers and it is expected that it can be used as an effort to increase milk production in postpartum mothers and to meet the needs of babies without having formula milk.